ACHIEVEMENT MOTIVATION FOR PSYCHOLOGY STUDENTS IN PARTICIPATING IN NATIONAL LEVEL ISLAMIC COMPETITIONS - Putri Nabila; Belly Lestari; Masayu Alifah Saznabila; Fahirah Mayangsari; Fatima Az-zahra; Bella Nafisah; Reski Ramadani; muhamad ilham fhatona; Fadhil Fadhlur Rohman; Sepriyan Pangestu; Winata ardiana; Filaila Dekautsar (CV. Doki Course and Training, 2023)
The purpose of this study was to determine why psychology students are motivated to participate in national level competitions. This research uses Mixed Method with sequential explanatory design the subject of this research comes from N = 150 psychology students. Taking the subject of this study using purposive sampling technique. Data collection techniques using questionnaires and using the achievement motive scale. The results of this study indicate that why psychology students are motivated to participate in national level competitions because of the drive in each individual to achieve goals such as wanting to challenge themselves There are several factors that influence individuals, namely ideals, self-development, parents, economy, school and the results of research from a total of N = 150 respondents based on factors found that as many as N = 25 have high motivation, N = 108 have moderate motivation, and N = 17 have low motivation whose results are more likely to be in the low category. When viewed from the gender of psychology students, both men have a motivation of (31.4889) and women have a motivation of (31.4095) which results in almost the same achievement motivation.